ANALISIS KEAMANAN WEBSITE PLANET KOMPUTER KEBUMEN MENGGUNAKAN METODE VULNERABILITY ASSESSMENT DENGAN TEMUAN 4 KERENTANAN TINGKAT MENENGAH: SECURITY ANALYSIS OF PLANET KOMPUTER KEBUMEN WEBSITE USING VULNERABILITY ASSESSMENT METHOD AND FINDINGS OF MEDIUM-LEVEL VULNERABILITIES - Muhamad Wafa Miftahul Anwar; Fahmi Fachri (LPPM Universitas Abdurrab, 2025)
This research aims to analyze the security of Planet Komputer Kebumen's website by applying the Vulnerability Assessment method. This approach was conducted to identify and evaluate potential security vulnerabilities in the website system. The research method consists of several stages: initial information gathering using Whois and Nmap, vulnerability scanning using OWASP ZAP 1.15.0, result analysis, and formulation of improvement recommendations. The research results show no high-risk vulnerabilities were found, however, 4 medium-level vulnerabilities, 4 low-level vulnerabilities, and 5 informational findings were identified. Major vulnerabilities include the absence of Content Security Policy, insecure transition from HTTP to HTTPS in forms, lack of anti-clickjacking headers, and suboptimal server security configurations. Based on these findings, improvement recommendations were formulated focusing on implementing appropriate security headers, protecting sensitive files, consistent use of HTTPS, and more secure cache and session management. This research demonstrates the importance of periodic security evaluations for SMEs to understand digital security risks and take appropriate preventive measures.